Study of the importance of national identity in the development of corporate social responsibility practices: A multivariate vision - Víctor Amor-Esteban; M-Purificación Galindo-Villardón; Fátima David (Administrative Sciences, 2018)
Corporate Social Responsibility (CSR) has the characteristic of being a truly global idea, and its global features could give rise to the assumption that national dynamics are secondary or even irrelevant. However, while CSR policies may be of a global nature, recent research suggests that lasting national institutions and distinctive ideological traditions determine corporate decisions. In this study, we analysed the 2004-2014 decade from a panel data sample of 6600 observations from 600 large, internationally listed companies, and based on multivariate statistical methods, we contrasted the relevance of national identity in the sustainable behaviour of companies with the discovery of important national discrepancies, which corroborates that the country of origin of companies offers a series of facilities and barriers for the development of CSR practices. Companies, depending on different pressures and expectations, care about what is important in their own country. Thus, the corporations coming from Nordic countries-recognised as welfare states-are presented as the leaders in sustainable behaviour, highlighting in the social aspect the proper treatment of their employees and interest groups. They are followed a step below by companies whose country of origin is located in Southern Europe, which prioritise environmental reports. Organisations whose headquarters are centralized in North American countries are in a very delayed position, especially in environmental performance, giving greater preference to ethical issues.
Keywords: 350; Corporate Social Responsibility (CSR); national identity; country of origin; multivariate statistics; social sustainability; sustainable development; environmental management